An innovative assembly to maintain isoflurane anaesthesia for dental procedure in rats - M., Hana; Chen, Hui Cheng; Radzi, R. (Veterinary Association Malaysia, 2017)
An innovative assembly to maintain isoflurane anaesthesia in rats is described. This assembly was used successfully in laboratory rats for dental procedures that may last as long as sixty minutes. Repeated exposures to isoflurane anaesthesia, of up to eight times within a 30-day study period in healthy laboratory rats did not result in any observable adverse-effects.